On practice and institution : new empirical directions - Lounsbury, Michael; Anderson, Deborah A.; Spee, Paul (Research in the sociology of organizations ;, 2021)
The concepts of practice and institution are of longstanding importance across the social sciences. This double-volume builds directly on the scholarship of Theodore Schatzki and Roger Friedland, to map out new theoretical and empirical directions at the interface between the practice and institutional "logics" literatures in organizational sociology, bridging the two perspectives. Volume 71 of Research in the Sociology of Organizations highlights a multitude of empirical directions suggesting particularly intriguing focal points for the emergent research agenda. The enclosed chapters grapple with issues related to the relationship of the symbolic and material aspects of culture and draw on a variety of empirical contexts (e.g. Islamic banking, Chinese manufacturing, and social innovation) to suggest different ways in which we might study social change at the interface of practice and institution.